ENZIMATIC PRODUCTION OF CHITOSAN FROM WASTE OF RAJUNGAN CRAB SHELL AND IT’S APLICATION IN CHOLESTEROL REDUCTION BY IN VITRO TEST - Alfian Nasir Maidin; Hasnah Natsir; Seniwati Dali (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2017)
This research aimed to show the percentages of the level of the cholesterol decreased by the convertion product of chitosan enzimatically through in vitro. The research method was started by the demineralization process of the sample in the form of powder of crab shells, and then continued with the de-colorization and de-proteination steps. The next step was de-asetilation enzymatically using de-acetylated chitin which had been isolated from Bacillus licheniformis HSA3-1a bacteria at 50OC for 2 hours until the chitosan was obtained. The research results indicated that the characteristics of the isolated chitosan had water content of 5.45%, ash content 1.53%, N-total of 6.99% and de-acetylation degree of 78.9%, and it showed white yellowish powder form. The results of the test of chitosan as the reducer of cholesterol level by in vitro process showed that 31.18% of the cholesterolwas decreased by 2 mg concentrate of chitosan. Beide, 0.5 mg of simvastatin (as positive control) had decreased by 58.29%.